2005
DOI: 10.1186/1467-4866-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Micro-spectroscopic investigation of selenium-bearing minerals from the Western US Phosphate Resource Area

Abstract: Mining activities in the US Western Phosphate Resource Area ͑WPRA͒ have released Se into the environment. Selenium has several different oxidation states and species, each having varying degrees of solubility, reactivity, and bioavailability. In this study we are investigating the speciation of Se in mine-waste rocks. Selenium speciation was determined using bulk and micro-x-ray absorption spectroscopy ͑XAS͒, as well as micro-x-ray fluorescence mapping. Rocks used for bulk-XAS were ground into fine powders. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 32 publications
1
34
3
Order By: Relevance
“…These values were similar to those obtained from and support the formation of either monoclinic [49] or red [43] elemental Se (Table 2).…”
supporting
confidence: 77%
“…These values were similar to those obtained from and support the formation of either monoclinic [49] or red [43] elemental Se (Table 2).…”
supporting
confidence: 77%
“…Figure 2 shows the normalized Se K-edge XANES spectra collected for a selection of model compounds with characteristic selenium valences. The Se K-edge position is sensitive to the valence of Se [3,[7][8][9][10]. In contrast to previous studies, no simple relation is found between the Se K-edge position and the selenium valence.…”
Section: Xafs Spectroscopycontrasting
confidence: 52%
“…However the edge position for Se(-I) (as in FeSe 2 and CuSe 2 ) is identical to that for elemental Se (~ 12659.7 eV in our study). We did not select the edge crest maxima to derive valences (see [10]) because this region is also affected by the local structures around Se. It is therefore unreliable for this purpose.…”
Section: Xafs Spectroscopymentioning
confidence: 99%
“…Energy calibration was performed by measuring a sample of metallic Se 0 and setting the K-edge, as determined by the maximum of the first derivative, to 12,658.0 eV. This value is consistent with those obtained in other studies [24][25][26]. All measured edge energies given in this publication were determined by this method.…”
Section: Selenium K-edge X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 90%